Transcriptomic Profiling of Thermotolerant Sarcomyxa edulis PQ650759 Reveals the Key Genes and Pathways During Fruiting Body Formation - Zitong Liu; Minglei Li; Hongyu Ma; Fei Wang; Lei Shi; Jinhe Wang; Chunge Sheng; Peng Zhang; Haiyang Yu; Jing Zhao; Yanfeng Wang (Journal of Fungi)
Sarcomyxa edulis is a characteristic low-temperature, edible mushroom in Northeast China. It has a delicious taste and rich nutritional and medicinal value. S. edulis can undergo explosive fruiting, neat fruiting, and unified harvesting, making it suitable for factory production. The molecular mechanisms underlying fruiting body development in S. edulis remain poorly understood. This study employed transcriptome analysis to compare the post-ripening mycelium (NPM) and primordial fruiting bodies (PRMs) of the thermostable S. edulis strain PQ650759, which uniquely forms primordia under constant temperature. A total of 4862 differentially expressed genes (DEGs) (|log2(fold change)| ≥ 1) were identified and found to be predominantly enriched in biological processes such as cell wall organization, DNA replication, and carbohydrate metabolism. KEGG pathway analysis revealed significant enrichment in 20 metabolic pathways, including mismatch repair, yeast cell cycle, and starch/sucrose metabolism. Ten candidate genes (e.g., SKP1, MRE11, GPI) linked to cell cycle regulation, DNA repair, and energy metabolism were randomly selected and prioritized for functional analysis. Quantitative PCR validation confirmed the reliability of transcriptome data, with expression trends consistent across both methods. Our findings provide critical insights into the molecular regulation of fruiting body development in S. edulis and establish a foundation for future mechanistic studies and strain optimization in industrial cultivation.